Community Structure of Macroalgae in the Coastal Waters of Tiwoho Village, Wori District, North Minahasa Regency - Iyanleba, Jonathan Yohanes; Kepel, Rene Ch.; Tombokan, John Leonard; Kondoy, Khristin F. I.; Mandagi, Stephanus Vianny; Kambey, Alex D. (Jurnal Ilmiah Platax, 2025)
The purpose of this study is to describe the morphology and anatomy of each macroalgae species and to analyze the community structure of macroalgae from the study location. Data collection was carried out using the Line Transect method with quadrat sampling techniques conducted at the lowest tide. Temperature measurement was done using a thermometer and salinity using a refractometer, while substrate determination was visually assessed based on the type of substrate. The results of this study found 7 species, consisting of 1 species of red algae, 4 species of brown algae, and 2 species of green algae. The morphology of these algae types varies with different anatomies based on cross and longitudinal sections of each part of the algal thallus. The highest species density was Turbinaria ornata (transect 1), while the lowest density was Halimeda opuntia and Sargassum polycystum (transect 1), Turbinaria ornata (transect 2 and transect 3). The macroalgae diversity index values on the three transects were in the medium category. The species evenness index values on the three transects were stable. The species richness index values on the three transects were in the low category. The dominance index values on the three transects were in the low category. Keywords: Macroalgae, Community, Transect, Quadrat, Tiwoho. Abstrak Tujuan penelitian ini adalah mendeskripsikan morfologi dan anatomi masing-masing spesies makroalga, dan menganalisis stuktur komunitas makroalga dari lokasi penelitian. Pengambilan data menggunakan metode Line Transect dengan teknik sampling kuadrat yang dilakukan pada saat surut terendah. Pengukuran suhu menggunakan Termometer dan salinitas menggunakan Refraktometer, dan untuk penentuan substrat dilihat secara visual jenis dari substrat tersebut. Hasil penelitian ini ditemukan 7 spesies yang terdiri dari 1 spesies alga merah, 4 spesies alga coklat dan 2 spesies alga hijau. Morfologi jenis-jenis alga tersebut beragam dengan anatomi yang berbeda berdasarkan potongan melintang dan memanjang dari masing-masing bagian thallus alga. Kepadatan spesies tertinggi yaitu Turbinaria ornata (transek 1) sedangkan kepadatan terendah yaitu Halimeda opuntia dan Sargassum polycystum (transek 1), Turbinaria ornata (transek 2 dan transek 3). Nilai indeks keanekaragaman makroalga pada ketiga transek termasuk dalam kategori sedang. Nilai indeks kemerataan jenis pada ketiga transek termasuk dalam keadaan stabil. Nilai indeks kekayaan jenis pada ketiga transek termasuk dalam kategori rendah. Nilai indeks dominasi pada ketiga transek termasuk dalam kategori rendah. Kata kunci: Makroalga, Komunitas, Transek, Kuadrat, Tiwoho.